The recombinant protein rSP03B is a valid antigen for screening dog exposure to Phlebotomus perniciosus across foci of canine leishmaniasis - Kostalova, T; Lestinova, T; Maia, C; Sumova, P; Vlkova, M; Willen, L; Polanska, N; Fiorentino, E; Scalone, A; Oliva, G; Veronesi, F; Cristóvão, J M; et al. (Medical and veterinary entomology, 2017)
The frequency of sandfly-host contacts can be measured by host antibody levels against sandfly salivary proteins. Recombinant salivary proteins are suggested to represent a valid replacement for salivary gland homogenate (SGH); however, it is necessary to prove that such antigens are recognized by antibodies against various populations of the same species. Phlebotomus perniciosus (Diptera: Psychodidae) is the main vector of Leishmania infantum (Trypanosomatida: Trypanosomatidae) in southwest Europe and is widespread from Portugal to Italy. In this study, sera were sampled from naturally exposed dogs from distant regions, including Campania (southern Italy), Umbria (central Italy) and the metropolitan Lisbon region (Portugal), where P. perniciosus is the unique or principal vector species. Sera were screened for anti-P. perniciosus antibodies using SGH and 43-kDa yellow-related recombinant protein (rSP03B). A robust correlation between antibodies recognizing SGH and rSP03B was detected in all regions, suggesting substantial antigenic cross-reactivity among different P. perniciosus populations. No significant differences in this relationship were detected between regions. Moreover, rSP03B and the native yellow-related protein were shown to share similar antigenic epitopes, as canine immunoglobulin G (IgG) binding to the native protein was inhibited by pre-incubation with the recombinant form. These findings suggest that rSP03B should be regarded as a universal marker of sandfly exposure throughout the geographical distribution of P. perniciosus.
Keywords: Portugalsko; psi; salivary proteins; antigeny; Dogs; Insect Bites and Stings; Salivary Proteins and Peptides; Insect Vectors; antibody response; hmyzí proteiny; Phlebotomus; Itálie; slinné proteiny a peptidy; Antigens; Recombinant Proteins; zvířata; rekombinantní proteiny; Mediterranean region; leishmanióza; hmyz - vektory; nemoci psů; kousnutí a bodnutí hmyzem; Dog Diseases; Leishmaniasis; sandflies; Leishmania infantum; Animals; dog; Italy; Portugal; Phlebotomus spp.; Insect Proteins; markers of exposure